NOT EVERY CRIME IS CRIMINAL ACT - Irfan Ardiansyah; Duwi Handoko; Rustam Rustam (Ensiklopedia of Journal, 2022)
If  I  say  that  crime  is  may  be  prosecuted  by  the  state  and  is  punishable  by  law.  Is  it  possible  to  commit  a  sin  can  be  punished  by  state  law?  For  simple  example  is  lie.  Lies  can  be  threatened  with  punishment  because  it  is  one  form  of  crime (fraud).  Lies  cannot  be  threatened  as  well  as  punishments  in  criminal  law  because  they  are  breach  of  contract  (defaults).  Even  though  within  of  criminal  law,  "perpetrators"  of  lies  can  be  punishment,  is  it  appropriate  to  punish  children  who  lie?  For  the  answer  to  this  question,  the  author  requested  an  agreement  from  the  readers  to  answer  it  within  of  religious  law.  When  legal  system  in  a  country  prohibits  evil  activities  (sin/crime),  these  criminals  can  overcome  this  by  traveling  to  other  country  where  such  evil  activities  are  legal  and  not  criminal  act.  I  call  it:  not  every  crime  is  criminal  act.